Eksplorasi Perkembangan Bahasa Anak Usia Dini: Analisa Faktor, Indikator, Dan Tahapan Perkembangan - Sofia Zahra; Masganti Sit (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2024)
Language development is one of the many areas of development that needs to be addressed in kindergarten. Language as a systematic and orderly system of pronunciation, ideas and emotions used for speaking, listening, reading and writing to communicate with other people. This research focuses on analysis related to early childhood language development, through the stages of development, the factors that influence children's language development, as well as indicators of children's language development and various theories of language development. The purpose of this research is to analyze matters related to children's normal development, this is because various problems often arise that children experience when they struggle with acquiring good language. The method used in this research is a qualitative method in the form of library research. The results of this research concluded that it is important to understand children's language development because the development of young children goes through 4 stages, namely pre-imgistic, single words, two-word sentences, and short sentences. Language and language development are important aspects of life, related to child development issues, the role of parents and teachers is an important factor in language development, because they must be good at stimulating children's language intelligence.